Pierre Robin syndrome: a case report - Gupta, Richa; Patel, Meena; Bajaj, Naresh (International Journal of Research in Medical Sciences, 2017)
Pierre Robin syndrome is characterized by micrognathia, glossoptosis and palatal malformation. We report a case of a 6 day neonate who presented with complaints of feeding and respiratory difficulty and was later diagnosed as case of Pierre Robin syndrome.